2020
DOI: 10.1038/s41598-020-76150-x
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime encoding in flow cytometry for bead-based sensing of biomolecular interaction

Abstract: To demonstrate the potential of time-resolved flow cytometry (FCM) for bioanalysis, clinical diagnostics, and optically encoded bead-based assays, we performed a proof-of-principle study to detect biomolecular interactions utilizing fluorescence lifetime (LT)-encoded micron-sized polymer beads bearing target-specific bioligands and a recently developed prototype lifetime flow cytometer (LT-FCM setup). This instrument is equipped with a single excitation light source and different fluorescence detectors, one op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…The long-lifetime td-FCM instrument measured the focused cells acoustically, and the throughput was lower compared to conventional cytometry. Similarly, Kage et al [ 69 ] developed a td-FCM system to measure the lifetime values of four types of quantum-dot-doped polymer beads. In this study, it was demonstrated that longer lifetimes of the quantum-dot-doped beads can be discriminated from shorter lifetimes found in dye-based beads by measuring the respective decay by separate tempo-spectral channels.…”
Section: Time-resolved Flow Cytometrymentioning
confidence: 99%
“…The long-lifetime td-FCM instrument measured the focused cells acoustically, and the throughput was lower compared to conventional cytometry. Similarly, Kage et al [ 69 ] developed a td-FCM system to measure the lifetime values of four types of quantum-dot-doped polymer beads. In this study, it was demonstrated that longer lifetimes of the quantum-dot-doped beads can be discriminated from shorter lifetimes found in dye-based beads by measuring the respective decay by separate tempo-spectral channels.…”
Section: Time-resolved Flow Cytometrymentioning
confidence: 99%
“…Spectral multiplexing identifies the analyte by its emission spectrum. Chia et al reported optical sectioning fluorescence microscopy using the spectral multiplexing method 89 . As shown in Fig.…”
Section: Fluorescence Imagingmentioning
confidence: 99%
“…Several groups have performed frequency-based lifetime flow cytometry by retrofitting lifetime channels into older cytometers [48] or have integrated flow-cells into a benchtop lifetime system [49]. The vast majority of the work in the literature focuses on lifetime flow cytometry of mammalian cells [50,51] although one article reports changing lifetime of EGFP expressing E. coli as they are phagocytized into macrophages [52]. The promise that lifetime-based viability measurements shows in this work should be transitioned to a lifetime flow cytometer so that the technique may meet its full potential.…”
Section: Statistical Computationsmentioning
confidence: 99%